THE EFFECT OF THE MARKETING MIX ON THE BEHAVIOR OF SHARIA COOPERATIVE MEMBERS IN USING SAVING PRODUCTS - Abu Bakar Akbar (JURNAL ILMIAH EDUNOMIKA, 2023)
The purpose of this research is to determine the effect of the marketing mix on the behavior of members of Islamic cooperatives in using savings products. The sharia cooperative which is the object of research here is KSPPS BMT Amanah Ummah. The research method in this study used quantitative methods, using questionnaires by distributing questionnaires to members of the KSPPS BMT Amanah Ummah. Source of data using primary and secondary flat. Data collection techniques, using questionnaires. Questionnaire is a data collection technique that is carried out by giving a set of questions and statements. Identity and variable questions are entered on a score scale of 1-5. The research results show that: 1) Products partially do not have a significant effect on behavior; 2) Price has no significant effect on behavior; 3) Place has no effect on behavior partially, place has no significant effect on behavior; 4) Promotion of behavior partially has a significant effect; 5) People towards the resulting behavior partially do not have a significant effect on behavior; 6) The process of behavior partially has a significant effect on behavior; and 7) Physical evidence of behavior partially does not have a significant effect on behavior. Based on hypothesis testing, the results of the analysis and discussion that have been completed are described, it can be concluded that product, price, place, promotion, people, process and physical evidence simultaneously influence the behavior of members of Islamic cooperatives.